Crossed fused renal ectopia in a Persian cat. Issue 1 (March 2017) - Seo, Sang-Hyuk; Lee, Hyun-A; Suh, Sang-Il; Choi, Ran; Park, In-Chul; Hyun, Changbaig
Case summary: This report describes a rare case of crossed fused renal ectopia (CFRE) in a cat. A mature intact male Persian cat presented with bloody nasal discharge and ascites. Diagnostic studies revealed an ectopic left kidney fused with an orthotopic right kidney and a concurrent feline infectious peritonitis (FIP) infection. The FIP was responsible for clinical signs in this cat, while clinical signs associated with CFRE were not obvious. Despite receiving intensive treatment, the cat died. A post-mortem examination was not performed because the owners declined approval. Relevance and novel information: To the best of our knowledge, this is the first report of L-shaped CFRE in a cat. In addition, this report describes the CT features of L-shaped CFRE in a cat.